Transparency of local government in Indonesia - I Made Pradana Adiputra; Sidharta Utama; Hilda Rossieta (Emerald Publishing Limited, 2018)
The purpose of this paper is to provide empirical evidence about the influence of the size of local government, the quality of local government financial statements, the level of local government response to the disclosure of financial information and the local political environment on the transparency of local government in Indonesia.The study sample consisted of 34 regional governments (provinces) in Indonesia in 2016, using purposive sampling and multiple regression analysis.The results showed that the quality of financial reporting through the audit opinion and political environment have a significant positive effect on the transparency of local government in Indonesia. On the other hand, the size of the local government and local government response rate on the regulation do not affect the transparency of local government in Indonesia.The agency, legitimacy and institutional theory have an important role in the underlying local government transparency practices in Indonesia. The results of this study should be used as the basis of thought and study to determine the factors that affect the performance of local governments from the financial and non-financial aspects.